Is there any radiation-induced brachial plexopathy after hypofractionated postmastectomy radiotherapy with helical tomotherapy? - Chomchai, Thinnakorn; Klunklin, Pitchayaponne; Tongprasert, Siam; Kanthawang, Thanat; Toapichattrakul, Piyapasara; Chitapanarux, Imjai (Frontiers in Oncology, 2024)
Introduction Radiation-induced brachial plexopathy (RIBP) is one of the most concerning late radiation effects after hypofractionated postmastectomy radiotherapy (HF-PMRT) to the chest wall and regional lymph nodes. The purpose of this study was to investigate the RIBP events occurring in breast cancer patients after HF-PMRT using intensity-modulated radiation therapy (IMRT) by helical tomotherapy. Furthermore, the dosimetric parameters of the ipsilateral brachial plexus were reported. Materials and methods Breast cancer patients who underwent HF-PMRT using the IMRT via HT at our institute were included. In the first cohort, subjective RIBP symptoms were measured using a QuickDASH questionnaire, whereas objective RIBP events were assessed using a comprehensive physical evaluation in the second cohort. The ipsilateral brachial plexus from all eligible patients’ treatment plans was contoured, and the dosimetric parameters were explored. Results From March 2014 to December 2022, 229 patients were enrolled; 107 and 72 individuals were in the first and second cohorts, respectively. The first cohort’s median follow-up period was 27 months, and the second cohort was 31 months. In the first cohort, 80 patients (74.77%) had a normal function, 21 (19.63%) had a mild grade, and 6 (5.61%) had a moderate grade; no severe or very severe RIBP was observed. However, the comprehensive physical evaluation of the second cohort indicated no RIBP events. Dosimetric analysis revealed that the median maximum dose was 44.52, 44.52, and 44.60 Gy; the median mean dose was 33.00, 32.23, and 32.33 Gy; and the median dose at 0.03 cc was 44.33, 44.36, and 44.39 Gy for all patients, patients in the first and second cohort, respectively. Each dosimetric parameter was evaluated, and no statistically significant differences were detected. Conclusion The absence of RIBP events supports the safety of employing HF-PMRT by HT for the chest wall and all regional lymph nodes. We propose that applying the ICRU Report 83 criteria for IMRT planning, which limit the maximum dose (107% of the prescribed dose) to less than 2% of the planning target volume and exclude the brachial plexus region from the maximal dose area, is a practical way to minimize the risk of RIBP from HF-PMRT.